2010
DOI: 10.1901/jaba.2010.43-101
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Variety of Foods Consumed by a Picky Eater: Generalization of Effects Across Caregivers and Settings

Abstract: A multiple baseline across settings was used to evaluate the effects of differential reinforcement of alternative behavior, nonremoval of the fork (Hoch, Babbitt, Coe, Krell, & Hackbert, 1994), and stimulus fading on consumption of food rejected previously. The study was conducted in two separate settings, and caregivers were trained in the intervention technique to increase generalization to natural settings. Food variety increased in both settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…Applied behaviour analysis, though largely focused on issues of social importance, has also centred on marketing-related behaviour, such as shopping and consumption behaviour (Barnard, Christophersen, &Wolf, 1977;Greene, Rouse, Green, & Clay, 1984;Sigurdsson, Saevarsson, & Foxall, 2009;Valdimarsdóttir, Halldórsdóttir, & Sigurđardóttir, 2010;Winett, Kramer, Walker, Malone, & Lane, 1988), alcohol consumption (Caudill & Lipscomb, 1980), and financial behaviour (Hantula & Crowell, 1994).…”
Section: Applied Behaviour Analysismentioning
confidence: 99%
“…Applied behaviour analysis, though largely focused on issues of social importance, has also centred on marketing-related behaviour, such as shopping and consumption behaviour (Barnard, Christophersen, &Wolf, 1977;Greene, Rouse, Green, & Clay, 1984;Sigurdsson, Saevarsson, & Foxall, 2009;Valdimarsdóttir, Halldórsdóttir, & Sigurđardóttir, 2010;Winett, Kramer, Walker, Malone, & Lane, 1988), alcohol consumption (Caudill & Lipscomb, 1980), and financial behaviour (Hantula & Crowell, 1994).…”
Section: Applied Behaviour Analysismentioning
confidence: 99%
“…Thus, diets lacking in important nutrients could lead to additional learning or behavior problems for children with ASD (Rosales et al, ). Fortunately, there are studies showing that we can improve the diet variety of children with ASD using applied behavior analysis (e.g., Ahearn, ; Kadey, Roane, Diaz, & Merrow, ; Laud, Girolami, Boscoe, & Gulotta, ; Levin, Volkert, & Piazza, ; Luiselli, Ricciardi, & Gilligan, ; Tarbox, Schiff, & Najdowski, ; Valdimarsdóttir, Halldórsdóttir, & SigurÐardóttir, ; Wood, Wolery, & Kaiser, ). For example, Kadey et al () expanded the diet variety of two participants diagnosed with ASD who were admitted to an intensive outpatient feeding program for treatment of food selectivity, using nonremoval of the spoon, noncontingent reinforcement, and a physical‐guidance procedure.…”
mentioning
confidence: 99%
“…For example, Kadey et al () expanded the diet variety of two participants diagnosed with ASD who were admitted to an intensive outpatient feeding program for treatment of food selectivity, using nonremoval of the spoon, noncontingent reinforcement, and a physical‐guidance procedure. Valdimarsdóttir et al () increased consumption of nonpreferred foods for one participant with ASD across multiple settings using nonremoval of the fork, differential reinforcement of alternative behavior, and stimulus fading. These studies used single‐case designs to evaluate the efficacy of the applied behavior analytic intervention.…”
mentioning
confidence: 99%
“…Valdimarsdottir, Halldorsdottir, and Sigurdar‐dottir (2010) showed that differential reinforcement of alternative behavior, nonremoval of the fork, and stimulus fading increased consumption of nonpreferred food for 1 child with autism in two settings and with caregivers. Anglesea, Hoch, and Taylor (2008) examined the effects of a pager prompt on the rapid eating of 3 teenagers with autism.…”
mentioning
confidence: 99%